Tingkat Stres Anak 6-8 Tahun Dalam Perawatan Gigi di RSGM Universitas Kristen Maranatha - Angeline Debora; Lie Fun Fun; Linda Sari Sembiring (Maranatha Christian University, 2022)
Dental care is a stressful event for children or adults. Fear of dentists and dental care has been seen as a major barrier in providing quality dental services. Fearful patients will avoid dental care and oral hygiene. School-age children need more intensive dental care because at that age there is a change of teeth and the growth of new teeth. However, dental care in children can cause stress, because they are afraid to face the dentist, the equipment used, the procedures, and so on. The purpose of this study was to describe the stress level of children 6-8 years in dental care at RSGM Maranatha Christian University. Sampling in this study uses non-probability sampling techniques and using accidental sampling. This study uses descriptive analytic research design and questionnaire data collection techniques. Subjects in this study were 71 patients aged 6-8 years. The results showed low stress levels in dental care including waiting to be called by a dentist (90.1%), dental examination (94.4%), dental fillings (86.5%), tooth extraction (79.3%). The value of the pulse rate in dental care which includes waiting to be called by a dentist, dental examination, dental fillings, tooth extraction has an average of 95.7 beats per minute (BPM) which is classified as normal. Based on visits, subjects who are old or new visitors alike experience relatively low stress. The conclusion of this study is that at the age of 6 and 7 years found more stress than at the age of 8 years. The pulse rate is normal but tends to increase during tooth extraction and the most common symptom experienced is cold palms. Keywords: dental care; pulse rate; stress level